Towards unmanned systems for dismounted operations in the Canadian Forces. (1st January 2011) - Beckman, Blake; Collier, Jack; Mackay, David; Monckton, Simon; Trentini, Michael; Wong, Franklin; Richard Bilodeau, Pierre
Unmanned systems are designed to reduce risk and magnify the impact of manned forces. Expanding unmanned involvement in military operations will require greater vehicle autonomy and the adoption of new concepts of operations. This paper discusses the technical challenges of unmanned systems in support of dismounted operations and research efforts by Defence R&D Canada to support unmanned vehicles in this role. New projects have been formulated to address these technical challenges.